Promoting Economic Recovery From the Perspective of Energy-Economic Resilience: Model Construction and Case Study - Wang, Yueren; Gong, Zaijing; Pan, Wei (Frontiers in Energy Research, 2020)
Energy is a basic resource for economic growth as well as an essential premise for economic recovery. The topic of resilience has recently been increasingly prominent in energy-economic domain, and has also entered policy discourse. Yet the measuring method of resilience based on the post-disruption event and the relationship of energy resilience and economic resilience are far from settled. This paper develops the idea of resilience and proposes a model to evaluate the economic recovery ability of an economy. It also proposes an inter-resilience decoupling model to address the impacts of energy-related elements on economic recovery. These ideas are then used for a preliminary empirical analysis of 14 countries against the context of 2007-2008 financial crisis.